Emerging antioxidant therapies in Friedreich’s ataxia - Edzeamey, Fred Jonathan; Ramchunder, Zenouska; Pourzand, Charareh; Anjomani Virmouni, Sara (Frontiers in Pharmacology, 2024)
Friedreich's ataxia (FRDA) is a rare childhood neurologic disorder, affecting 1 in 50,000 Caucasians. The disease is caused by the abnormal expansion of the GAA repeat sequence in intron 1 of the FXN gene, leading to the reduced expression of the mitochondrial protein frataxin. The disease is characterised by progressive neurodegeneration, hypertrophic cardiomyopathy, diabetes mellitus and musculoskeletal deformities. The reduced expression of frataxin has been suggested to result in the downregulation of endogenous antioxidant defence mechanisms and mitochondrial bioenergetics, and the increase in mitochondrial iron accumulation thereby leading to oxidative stress. The confirmation of oxidative stress as one of the pathological signatures of FRDA led to the search for antioxidants which can be used as therapeutic modality. Based on this observation, antioxidants with different mechanisms of action have been explored for FRDA therapy since the last two decades. In this review, we bring forth all antioxidants which have been investigated for FRDA therapy and have been signed off for clinical trials. We summarise their various target points in FRDA disease pathway, their performances during clinical trials and possible factors which might have accounted for their failure or otherwise during clinical trials. We also discuss the limitation of the studies completed and propose possible strategies for combinatorial therapy of antioxidants to generate synergistic effect in FRDA patients. treatment modality for FRDA (Lee, 2023). FRDA is caused by the abnormal expansion of the Guanine-Adenine-Adenine (GAA) repeat sequence in intron 1 of the FXN gene (Anjomani Virmouni et al., 2015, Campuzano et al., 1996). The FXN gene codes for a very important mitochondrial protein called frataxin (Cotticelli et al., 2022, Huichalaf et al., 2022). Frataxin is highly conserved in nature with homologs in mammals, plants, yeast and invertebrates. This 14KDa protein is synthesised in the cytoplasm and, following cleavage by mitochondrial processing peptidase (MPP) to obtain the mature frataxin, is transported to the mitochondrial matrix (